Impact of type 2 diabetes variants identified through genome-wide association studies in early-onset type 2 diabetes from South Indian population - Samuel Liju; Manickam Chidambaram; Viswanathan Mohan; Venkatesan Radha (Genomics & Informatics)
The prevalence of early-onset type 2 diabetes (EOT2D) is increasing in Asian countries. Genome-wide association studies performed in European and various other populations have identified associations of numerous variants with type 2 diabetes in adults. However, the genetic component of EOT2D which is still unexplored could have similarities with late-onset type 2 diabetes. Here in the present study we aim to identify the association of variants with EOT2D in South Indian population. Twenty-five variants from 18 gene loci were genotyped in 1,188 EOT2D and 1,183 normal glucose tolerant subjects using the MassARRAY technology. We confirm the association of the HHEX variant rs1111875 with EOT2D in this South Indian population and also the association of CDKN2A/2B (rs7020996) and TCF7L2 (rs4506565) with EOT2D. Logistic regression analyses of the TCF7L2 variant rs4506565(A/T), showed that the heterozygous and homozygous carriers for allele ‘T’ have odds ratios of 1.47 (95% confidence interval [CI], 1.17 to 1.83; p = 0.001) and 1.65 (95% CI, 1.18 to 2.28; p = 0.006) respectively, relative to AA homozygote. For the HHEX variant rs1111875 (T/C), heterozygous and homozygous carriers for allele ‘C’ have odds ratios of 1.13 (95% CI, 0.91 to 1.42; p = 0.27) and 1.58 (95% CI, 1.17 to 2.12; p = 0.003) respectively, relative to the TT homozygote. For CDKN2A/2B variant rs7020996, the heterozygous and homozygous carriers of allele ‘C’ were protective with odds ratios of 0.65 (95% CI, 0.51 to 0.83; p = 0.0004) and 0.62 (95% CI, 0.27 to 1.39; p = 0.24) respectively, relative to TT homozygote. This is the first study to report on the association of HHEX variant rs1111875 with EOT2D in this population.